Peer Review of Teaching. - Sachs, Judyth; Parsell, Mitch; Jacenyik-Trawoger, Christa (Office for Learning and Teaching, 2013)
Handbook resulting from a project that focused on the social, communicative and interpersonal (SCI) skills required to be an effective leader in higher education, examined through the lens of peer review. The project provided two tightly connected outcomes: a theoretical understanding of what it means become a leader, and a range of resources for participants to test, re-test and practice leadership skills. The resources focus on leadership as a process, as well as an outcome. The project sought to: (1) build communities of practice at global, institutional and local levels, devoted to the quality enhancement of leadership and teaching, (2) provide stakeholders with a non- threatening environment in which to practise the skills needed to maintain peer review relationships, (3) develop a national and international network against which to benchmark and share information, and (4) develop a rich pool of practical resources and research literature on leadership skills in higher education.